Efektivitas Kebijakan Pemerintah Daerah Dalam Mendorong Pembangunan Ekonomi Melalui Pengembangan Ekowisata Di Kabupaten Berau - Ira Indriani (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
This study aims to evaluate the effectiveness of local government policies in promoting sustainable economic development through the development of ecotourism in Berau Regency, East Kalimantan. Berau Regency is known for its significant potential in the ecotourism sector, particularly with prominent destinations such as the Derawan Islands and Labuan Cermin Village. The local government has adopted several strategic policies, outlined in documents such as RIPPDA and RPJMD, to support the development of sustainable ecotourism. However, the effectiveness of these policies remains uncertain, especially in terms of implementation, equitable distribution of benefits, and environmental conservation. This study employs a descriptive qualitative approach, utilizing data collection methods such as in-depth interviews, policy document analysis, and field observations. The findings indicate that, although the policies align with the principles of sustainable development, their implementation faces significant challenges. In particular, local community involvement is uneven, environmental conservation efforts are insufficient, and coordination between stakeholders is suboptimal. Analysis through public policy theory, sustainable development theory, and ecotourism theory reveals that the existing policies, while normative, are not sufficiently effective in achieving inclusive and sustainable development goals. Therefore, improvements in governance, capacity building for local communities, and enhanced evaluation and monitoring mechanisms are necessary to ensure that ecotourism policies in Berau Regency contribute to sustainable and equitable economic development.